Characterizing the content and quality of internet resources on exercise training in Ehlers-Danlos Syndromes and generalized hypermobility spectrum disorder - Jillian Dhawan; Sahar Sohrabipour; Ali Salman Al-Timimi; Brenawen Elangeswaran; Omer Choudhary; Noor Al Kaabi; Megha Ibrahim Masthan; Daniel Santa Mina; Laura McGillis; Wing Ting Truong; Encarna Camacho Perez; Jane Schubart; et al. (PLoS ONE, 2025)
Background Individuals with Ehlers-Danlos Syndromes (EDS) and Generalized Hypermobility Spectrum Disorder (G-HSD) experience musculoskeletal joint instability, cardiopulmonary manifestations, and functional limitations with online exercise resources commonly utilized. This study characterizes and assesses the content, quality, and readability of websites addressing exercise training for individuals with EDS/G-HSD. Methods The first 350 English websites were Googled using search terms “Ehlers-Danlos Syndrome and exercise” and “Ehlers-Danlos Syndrome and physical activity,” targeting educational/instructional sites on exercise training for adults with EDS/G-HSD. Content was assessed using scientific consensus criteria, quality using Modified DISCERN, Global Quality Scale (GQS), and the Patient Education Materials Assessment Tool (PEMAT), and readability using Flesch-Kincaid Grade Level (FKGL) and Flesh-Reading Ease Scores (FRES). Results 78/350 unique websites were included, most from industry organizations (37%) and personal commentary (24%). The mean content score was moderate 13.8 ± 4.4/25. The content most discussed included: short/long-term benefits of muscle strength, resistance training, and generalized exercise safety considerations. Median modified DISCERN and GQS scores were 4/5 IQR [3–4] and 3/5[2.3–4], respectively. Mean PEMAT understandability and actionability scores were 85% ± 12% and 69% ± 23%, respectively. Average FKGL was 11.0 ± 2.7 and FRES was 43.6 ± 7.2. Moderate-strong Spearman correlations were observed between total content scores and GQS (rho = 0.76) and DISCERN (rho = 0.52), p < 0.001 for both. Conclusion Website content varied, most addressing general safety recommendations and multiple training modalities. While quality was moderate-to-good, future resources should focus on simplified language, actionable guidance, and visual aids. Incorporating practical examples of daily activities, injury prevention strategies, broader benefits like cardiovascular health, and psychological support can empower safe and confident exercise training.